Glycerine Treated Nanofibrillated Cellulose Composites. (19th April 2016) - Erbas Kiziltas, Esra; Kiziltas, Alper; Nazari, Behzad; Gardner, Douglas J.; Bousfield, Douglas W.
Abstract : Glycerine treated nanofibrillated cellulose (GNFC) was prepared by mixing aqueous nanofibrillated cellulose (NFC) suspensions with glycerine. Styrene maleic anhydride (SMA) copolymer composites with different loadings of GNFC were prepared by melt compounding followed by injection molding. The incorporation of GNFC increased tensile and flexural modulus of elasticity of the composites. Thermogravimetric analysis showed that as GNFC loading increased, the thermal stability of the composites decreased marginally. The incorporation of GNFC into the SMA copolymer matrix resulted in higher elastic modulus (G ′ ) and shear viscosities than the neat SMA copolymer, especially at low frequencies. The orientation of rigid GNFC particles in the composites induced a strong shear thinning behavior with an increase in GNFC loading. The decrease in the slope of elastic modulus with increasing GNFC loading suggested that the microstructural changes of the polymer matrix can be attributed to the incorporation of GNFC. Scanning electron microscopy (SEM) images of fracture surfaces show areas of GNFC agglomerates in the SMA matrix.